Towards field-effect controlled graphene-enhanced Raman spectroscopy of cobalt octaethylporphyrin molecules. (22nd February 2021) - Sleziona, Stephan; Rauls, Simon; Heckhoff, Tobias; Christen, Leonard; Pollmann, Erik; Madauß, Lukas; Franzka, Steffen; Lorke, Axel; Wende, Heiko; Schleberger, Marika
Abstract: During the last decade graphene-enhanced Raman spectroscopy has proven to be a powerful tool to detect and analyze minute amounts of molecules adsorbed on graphene. By using a graphene-based field-effect device the unique opportunity arises to gain a deeper insight into the coupling of molecules and graphene as graphene's Fermi level can be controlled by the transistor`s gate voltage. However, the fabrication of such a device comes with great challenges because of contaminations stemming from processing the device inevitably prevent direct adsorption of the molecules onto graphene rendering it unsuitable for field-effect controlled graphene-enhanced Raman spectroscopy measurements/experiments. In this work, we solve this problem by establishing two different fabrication procedures for such devices, both of which are in addition compatible with large area and scalable production requirements. As a first solution, selective argon cluster irradiation is shown to be an efficient way to remove resist residues after processing. We provide evidence that after the irradiation the enhancement of the molecular Raman signal can indeed be measured, demonstrating that this procedure cleans graphene's surface sufficiently enough for direct molecular adsorption. As a second solution, we have developed a novel stacking method to encapsulate the molecules in between two graphene layers to protect the underlying graphene and molecular layer from the harsh conditions during the photolithography process. This method combines the advantages of dry stacking, which leads to a perfectly clean interface, and wet stacking processes, which can easily be scaled up for large area processing. Both approaches yield working graphene transistors with strong molecular Raman signals stemming from cobalt octaehtylporphyrin, a promising and prototypical candidate for spintronic applications, and are therefore suitable for graphene based molecular sensing applications.